The Use of Problem-based Learning Models and Media in Geography Learning - Mutia Ayulanda; Yurni Suasti; Ernawati Ernawati (Postgraduate School, Universitas Negeri Padang, 2021)
The purpose of this study is to: 1) know the use of Problem Based Learning; 2) know the various ways of applying Problem Based Learning; and 3) know the use of media in learning. This research is a library research. Literature research is research whose data collection techniques are carried out by reading various literature related to information and relevance to research topics. Problem-based learning, hereinafter abbreviated as PBL, is one of the innovative learning models that can provide active learning conditions to students and the purpose of using learning media is to help teachers in conveying messages or subject matter to their students, so that the message is easier to understand, more interesting, and more enjoyable to students.